Ankyloglossia and Lingual Frenotomy: National trends in diagnosis and management in the United States, 1997-2012 - Walsh, Jonathan (Otolaryngol Head Neck Surg, 2017)
OBJECTIVES: Describe trends in diagnosis of ankyloglossia and use of lingual frenotomy, and analyze patient and hospital-level factors compared to the total pediatric discharge population. STUDY DESIGN: Retrospective analysis METHODS: We reviewed available data from years 1997 to 2012 using the Kidś Inpatient Database (KID), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality. All weighted pediatric discharges with ankyloglossia, newborn feeding difficulty, or lingual frenotomy were analyzed for variables of sex, payer, zip code median income, hospital ownership, location/teaching status, bed size, region, and children’s hospital status. Chi(2) analysis with 95% confidence intervals and Odds Ratio were used to identify differences between the study group and the total database discharge population. RESULTS: Diagnosis of ankyloglossia increased each year with N of 3934, 5430, 7785, 11397, 19459, and 32837 children respectively, with the largest increase in the last 6 years. Similarly, frenotomy increased with N of 1279, 1633, 2538, 3988, 6900, and 12406 procedures. Compared to the total discharge population, children with ankyloglossia or frenotomy, respectively, were more often male (63.6% ankyloglossia, 65.3% frenotomy vs 51.2%), privately insured (60.1%, 62.1% vs 43.6%), from higher income zip code (78.1%, 78.2% vs 68.6%), and lived in Midwest region (29.3%, 32.3% vs 21.7%). CONCLUSION: These pilot data show increases in diagnoses of ankyloglossia and use of frenotomy. There is a preponderance of children who are male, privately-insured, or Midwest residents being diagnosed and treated for ankyloglossia. This broad variation may reflect local practice patterns, or imply cultural and socioeconomic bias.